2012
DOI: 10.1111/j.1439-0531.2012.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Maternal Immune System During Pregnancy in the Cow

Abstract: Contents There is a molecular crosstalk between the trophoblast and maternal immune cells of bovine endometrium. The uterine cells are able to secrete cytokine/chemokines to either induce a suppressive environment for establishment of the pregnancy or to recruit immune cells to the endometrium to fight infections. Despite morphological differences between women and cows, mechanisms for immune tolerance during pregnancy seem to be conserved. Mechanisms for uterine immunesuppression in the cow include: reduced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 115 publications
(235 reference statements)
2
39
0
Order By: Relevance
“…In the present study, intravaginal immunization was not effective in preventing uterine diseases, suggesting that mucosal immunization of the vagina, considering dose and composition used, does not affect the immunological status of the uterus. Nevertheless, it is important to highlight that the uterus is an immune tolerant environment during pregnancy [51], and this might have prevented the uterus to develop an immune response to the intravaginal vaccines. Further investigation is needed to evaluate if intravaginal vaccination administered prior to pregnancy would elicit a uterine immune response capable of prevent uterine diseases, and conclude if local synthesis of specific antibodies by the uterine mucosa is important for the prevention of puerperal metritis and endometritis in heifers.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, intravaginal immunization was not effective in preventing uterine diseases, suggesting that mucosal immunization of the vagina, considering dose and composition used, does not affect the immunological status of the uterus. Nevertheless, it is important to highlight that the uterus is an immune tolerant environment during pregnancy [51], and this might have prevented the uterus to develop an immune response to the intravaginal vaccines. Further investigation is needed to evaluate if intravaginal vaccination administered prior to pregnancy would elicit a uterine immune response capable of prevent uterine diseases, and conclude if local synthesis of specific antibodies by the uterine mucosa is important for the prevention of puerperal metritis and endometritis in heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, ~2,000 microRNAs have been described in human [78] microRNAs have been reported to play important role in in cellular and developmental processes, including developmental timing, organ development, differentiation, proliferation, apoptosis and immune regulation [67]. Recently, Taylor and his colleagues reported the presence of diagnostic miRNAs from EpCAM-positive exosomes from ovarian cancer patients’ serum [12].…”
Section: Introductionmentioning
confidence: 99%
“…Immune-physiological reproductive evidence suggests that increased numbers of γδ T-cells in endometrial luminal epithelium are not only dependent upon conceptus stimulus (Tekin and Hansen, 2004) but also on systemic signals (i.e. maternal blood circulation; Majewski et al, 2001;Oliveira et al, 2012). In immune-modulating in vitro assays (Holderness et al, 2007) with apple CT (i.e.…”
Section: Characterization Of Ctmentioning
confidence: 99%
“…It is also likely that protein mediators (i.e. limphokines) produced by epithelial uterine lymphocytes induce regulatory dynamics on IFN-τ and IFN-γ (Oliveira et al, 2012). However, although the function of γδ T-lymphocyte on early maternal − embryonic and embryonic − foetal interfaces is not clear, Holderness et al (2007) and Jutila et al (2008) suggested that CT (i.e.…”
Section: Potential Benefits Of Ctmentioning
confidence: 99%